SUPPORT TO TEACHERS' PROFESSIONAL DEVELOPMENT IN UKRAINE AND ENGLAND: EVIDENCE FROM TALIS SURVEY - Ilona Palaguta (Pavlo Tychyna Uman State Pedagogical University, 2019)
In the article the basic problems of the pedagogical support of teacher's professional development in Ukraine and England are analyzed. In the process of future teacher's professional development, qualified teachers should support young teachers, because they do not have an experience, the knowledge of human nature, skills of self- organization and self-regulation. It is very important to know the teachers' needs in professional development for helping them to solve difficulties, which will appear in their professional life, to expand and extend their knowledge and skills, obtained during their training at the university and provide a basis for constant professional development. A comparative analysis of the needs of Ukrainian and English teachers in their professional development is described. In our view, a comparative analysis of the needs of Ukrainian and English teachers in their professional development might be important since in Ukraine the issue of teachers' professional development has been investigated, but there is still much to be considered. Thus, it will be useful to address the foreign experience in such a question, especially to the experience of Great Britain where teachers continuous professional development is of top priority. Learning International Survey (TALIS) conducted in Ukraine and England is characterized. In Ukraine, the Ukrainian Educational Research Association conducted the survey based on TALIS methodology in 2017. The aim of it is to study the educational environment and conditions of teachers' work: identification of teachers' training and professional development, studying the nature of school's culture, analysis of values and professional ideas of teachers. Three main TALIS questionnaires items are enumerated. The main focus of attention to be taken into account the teachers' awareness of what mentoring is and what forms and functions are meant by it is raised. The new Conception of Pedagogical Education Development in Ukraine takes into account both pre-service and in-service teachers' education [5]. It is presented as an internship period. According to the above-mentioned document, novice teachers work under the supervision of experienced teachers.